Leukopenia, Hypomagnesemia in 2,4-D Poisoning-A Rare Presentation (Indian Journal of Forensic Medicine & Toxicology, 2020)
2,4-D(2,4-Dichlorophenoxyaceticacid) is a common herbicide in agriculture field. It has moderately toxiceffect on mammals.2,4-D is available either in salt or ester formulations for field level use .Although nospecific antidote available for this herbicide, forced alkaline diuresis is one of the modalities of treatmentto promote early excretion of toxin through kidney and minimize its complications .Other management areessentially supportive measure and prevention of possible complications like aspiration pneumonia .Thereare a numbers of complications that are reported in varying degree .It affects skeletal muscle ,cardiovascular,gastrointestinal , renal ,central and peripheral nervous system. Here we report a case who developed unusualcomplications like leukopenia, hypomagnesemia, proximal muscle weakness after consumption of 2,4-Dafter suicidal intent.